Optimization of poultry offal and extender levels for cost-effective chicken sausage production (Bangladesh Journal of Animal Science, 2025)
The research was carried out to examine the use of consumable broiler and spent hen offal in raw chicken meat to prepare chicken meat sausages. For preparing chicken meat sausages, along with edible poultry parts such as skin, liver, gizzard, and heart were used at 15%, 20% and 25% levels whereas extenders used at 25%, 30% and 35% respectively. These sausages were tested for quality and sensory characteristics. The chicken meat sausages with 15% consumable offal and 25% extenders had demonstrated significantly (p